Analisis Kemampuan HOTS Siswa pada Materi Trigonometri Ditinjau dari Gaya Belajar David Kolb - Gunawan Gunawan; Aprilia Nurul Chasanah; Zuida Ratih Hendrastuti; Wahyu Prihatiningrum (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
The purpose of this study was to analyze students' HOTS abilities on trigonometric material based on learning styles. This research is a qualitative descriptive study. The research subjects were 34 students of class XI MIPA 2 in MAN 2 Magelang. The instrument used was a test instrument. Data analysis was performed through data reduction, data presentation, and concluding. HOTS ability of students in learning styles is divergent, the subject can analyze and evaluate indicators but the subject has not been able to create indicators. HOTS ability of students learning style assimilation, the subject can evaluate indicators but not yet able to analyze and create indicators. HOTS ability of students in convergent learning styles, the subject can analyze and evaluate indicators but not yet able to analyze indicators. HOTS ability of students in the learning style of accommodation, the subject can analyze and evaluate indicators but not yet able to create indicators.